Pelatihan Pemanfaatan Aplikasi Mentimeter dalam Mengembangkan Kompetensi Mengajar Guru di Yayasan Attaqwa 08 Karang Tengah, Bekasi - Syamsi Setiadi; Andri Ilham; Puty Zulharby; Ihwan Rahman Bahtiar; Fatwa Arifah; Muhammad Kamal; Ahmad Marzuq (Lembaga Peneliian dan Pengabdian Masyarakat (LPPM) Universitas Islam Madura (UIM), 2023)
The development of learning media, especially learning evaluation media, during the Covid-19 pandemic brought new directions in the learning process. Based on the results of the needs analysis, most teachers at the Attaqwa 08 Karang Tengah Foundation are proficient in using zoom and google forms to organize the learning process. However, problems arised when 73.3% of teachers still use printed books, 42% use PowerPoint, 10% take videos from YouTube, and only 10% make videos to explain learning materials. As many as 63% of teachers want application-based, smartphone-based, or online-based learning development training, especially learning evaluation applications. The Mentimeter platform is a solution that can be offered to these teachers. Mentimeter offers convenience in making learning evaluations with a variety of attractive displays with very diverse animations. The training program was carried out for 2 days with workshop and mentoring methods and was attended by 50 participants. The results of the activity showed that participants gained new insights that were useful in enhancing creative and innovative learning.